Accurate computations with Laguerre matrices. Issue 1 (5th October 2018) - Delgado, Jorge; Orera, Héctor; Peña, Juan Manuel
Summary: This paper provides an accurate method to obtain the bidiagonal factorization of collocation matrices of generalized Laguerre polynomials and of Lah matrices, which in turn can be used to compute with high relative accuracy the eigenvalues, singular values, and inverses of these matrices. Numerical examples are included.